Development of Natural Disaster Mitigation LKPD Based on PJBL-STEM Assisted by Micro: Bit to Increase Self Awareness and Creative Problem Solving - Ayu Nurjanah; Kartini Herlina; Chandra Ertikanto (Postgraduate, University of Mataram, 2023)
This research aims to validate the PJBL-STEM-based natural disaster mitigation worksheet assisted by Micro: bit that has been developed. Validation was carried out by three experts, two of whom were academic experts in the field of education, and the other person was a teacher as a practitioner expert. The validation results show that the worksheet developed is very valid. The content validity of the worksheet obtained an average validity percentage weight of 89.1%, which was categorized as very valid; this shows the vital relevance of the content to learning objectives related to mitigating natural disasters due to global warming. The validity of the language aspect obtained an average weighted percentage of validity of 89.6%, which is categorized as very valid and shows excellent language quality and communication skills. Finally, the media and design's validity consists of cover and content aspects. The cover design received an average validity percentage of 93.5%, and the content design obtained an average validity percentage of 91.7%, so both are categorized as very valid. This confirms that the design of the worksheet, both the cover and the presentation of the contents, is perfect. These findings highlight that these worksheets maintain high-quality content, language, and design standards.